2021
DOI: 10.1111/dom.14545
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐dependent insulinotropic polypeptide induces lipolysis during stable basal insulin substitution and hyperglycaemia in men with type 1 diabetes: A randomized, double‐blind, placebo‐controlled, crossover clinical trial

Abstract: Glucose-dependent insulinotropic polypeptide (GIP) plays an important role in the glucose and lipid metabolism. We investigated the effects of exogenous GIP on lipid metabolism during time of stable insulin levels. Ten male patients with type 1 diabetes without endogenous insulin secretion (C-peptide-negative, mean [±SD] age 26 ± 4years, body mass index 24 [±2] kg/m 2 , glycated haemoglobin 56 [±8] mmol/mol or 7.3 [±0.8]%) were studied in a randomized, double-blind, placebo-controlled, crossover study with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Other studies reported either lipolytic or lipogenic action of GIP, depending on the obesity status or glucose tolerance [ 2 , 3 , 4 , 26 , 27 ]. GIP infusion was found to induce lipolysis, shown as increased plasma NEFA and glycerol concentrations, during stable basal insulin substitution and hyperglycemia in men with type 1 diabetes [ 28 ]. The results are consistent with the NEFA changes observed in high GIP group after reducing plasma GIP level in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported either lipolytic or lipogenic action of GIP, depending on the obesity status or glucose tolerance [ 2 , 3 , 4 , 26 , 27 ]. GIP infusion was found to induce lipolysis, shown as increased plasma NEFA and glycerol concentrations, during stable basal insulin substitution and hyperglycemia in men with type 1 diabetes [ 28 ]. The results are consistent with the NEFA changes observed in high GIP group after reducing plasma GIP level in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…Es wird diskutiert, dass der GIP-Agonismus, indem er die Lipidpufferkapazität des wATs verbessert, die Fettansammlung in anderen Organen (ektope Lipidspeicherung) reduzieren kann [57,58]. Erst kürzlich wurde in Clamp-Versuchen gezeigt, dass GIP bei Patienten/Patientinnen mit Typ-1-Diabetes und bei niedrigen Insulinspiegeln Plasmaglyceride und freie Fettsäuren erhöht, was auf eine direkte lipolytische Wirkung von GIP bei hohen Glukosespiegeln und niedrigen Plasmainsulinspiegeln hinweist [69]. Zusätzlich wird daher angenommen, dass GIP eine wichtige Rolle bei der Adipositas spielt, auch wenn die biologische Wirkung von GIP noch nicht ausreichend verstanden ist.…”
Section: Wirkungen Von Gip Und Glp-1 Im Fettgewebeunclassified
“…36,37 GIP plays an important role in the regulation of food intake, lipoprotein lipase activity and fat decomposition during carbohydrate/fat degradation in adipose tissue; it produces a direct lipolytic effect during hyperglycaemia and low levels of insulin. 38 Elimination of GIPR activity by various mechanisms, including genetic ablation blockage, GIPR antagonist or neutralization of GIPR, has a favourable effect on glucose tolerance and obesity. [39][40][41][42] GIPR antagonists have been developed as treatments for T2D and obesity.…”
Section: Gip (Secreted By K-cells In the Upper Segment Of The Small I...mentioning
confidence: 99%
“… 36 , 37 GIP plays an important role in the regulation of food intake, lipoprotein lipase activity and fat decomposition during carbohydrate/fat degradation in adipose tissue; it produces a direct lipolytic effect during hyperglycaemia and low levels of insulin. 38 …”
Section: Gip-r Activitymentioning
confidence: 99%